2010
DOI: 10.1117/1.3374049
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative delineation of primary brain tumors using time-resolved fluorescence spectroscopy

Abstract: The goal of this study is to determine the potential of time-resolved laser-induced fluorescence spectroscopy (TR-LIFS) as an adjunctive tool for delineation of brain tumor from surrounding normal tissue in order to assist the neurosurgeon in near-complete tumor excision. A time-domain TR-LIFS prototype apparatus (gated photomultiplier detection, fast digitizer) was used for recording tissue autofluorescence in normal cortex (NC), normal white matter (NWM), and various grades of gliomas intraoperatively. Tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 33 publications
7
91
3
Order By: Relevance
“…The potential fast data acquisition (e.g., ns laser pulses) thus provides a unique advantage for clinical applications [51]. For example, flexible fiber probes can be coupled to endoscopy systems for clinical surveillance [52][53][54][55][56]. Multiple time-resolved spectra can either be acquired by sequentially scanning in the spectral domain (e.g., via a monochromator) [57] or using a multiple fiber delay arrangement [58].…”
Section: Pulse Sampling Techniquesmentioning
confidence: 99%
“…The potential fast data acquisition (e.g., ns laser pulses) thus provides a unique advantage for clinical applications [51]. For example, flexible fiber probes can be coupled to endoscopy systems for clinical surveillance [52][53][54][55][56]. Multiple time-resolved spectra can either be acquired by sequentially scanning in the spectral domain (e.g., via a monochromator) [57] or using a multiple fiber delay arrangement [58].…”
Section: Pulse Sampling Techniquesmentioning
confidence: 99%
“…Changes in the fluorescence properties of these molecules can report on altered metabolism, protein cross links, cell signalling and even disease state [15,[17][18][19]. In particular the fluorescence lifetime of endogenous fluorophores, which is relatively insensitive to fluorophore concentration and to signal attenuation by the sample, has been shown (both ex vivo and in vivo) to effectively differentiate between healthy and diseased tissue, for example in atherosclerotic plaques [20,21] and in various types of cancer [22][23][24][25][26][27][28][29][30][31]. Accordingly, there is significant interest in the development of instruments that can measure the autofluorescence properties of skin for clinical diagnosis, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The system required a relatively long data acquisition time (∼30 s) to capture each tissue measurement, which would need to be shortened substantially for effective integration in clinical workflows. 79 Vasefi et al 80 recently reported on an improved TR-FS system with near real-time data acquisition and classification. In this study, tissue differentiation on larger tissue samples measured in vivo NC (n ¼ 10), WM (n ¼ 12), and GBM (n ¼ 13) with nine patients is described.…”
Section: Time-domain Fluorescence Measurement Methodsmentioning
confidence: 99%